Integrated FAHP, ARAS-F and MSGP methods for green supplier evaluation and selection - Liao, Chin-Nung; Fu, Yan-Kai; Wu, Li-Chun (Technological and Economic Development of Economy, 2016)
In recent years, determining the best supplier in the green supply chain has become a key strategic task for a firm. Since the decision usually involves several objectives or criteria, the green supplier selection process is a fuzzy multiple criteria decision-making (FMCDM) problem. Considering both qualitative and quantitative criteria, this study proposes new integrated fuzzy techniques for fuzzy analytic hierarchy process (FAHP), fuzzy additive ratio assessment (ARASF) and multi-segment goal programming (MSGP) approach to solve the green supplier selection problems. The advantage of this method is that it allows decision makers to set multiple segment aspiration levels for green supplier selection problems. The integrated model is illustrated by an example in a watch firm.First published online: 03 Nov 2015